Effects of Dietary Intervention on Inflammatory Markers in Metabolic Syndrome: A Systematic Review and Meta-Analysis - Wang, Mengjun; Liu, Junliang; Zhang, Zhao; Zhang, Haixiong; Wang, Ning; Chen, Xi; Han, Xuemei; Lu, Qian; Chi, Shanshan (Frontiers in Nutrition, 2022)
Background: The dietary intervention may modulate inflammatory indicators, but the correlations between dietary intervention and inflammatory markers in metabolic syndrome (MetS) settings remain opaque. Objective： To evaluate the effects of dietary intervention on interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and C-reactive protein (CRP) in patients with MetS by systematic review and meta-analysis. Methods: Database including PubMed, Embase, Cochrane Library, Scopus, and Google scholar were searched from June 2011 to June 2021 for relevant available articles. Standardized mean difference (SMD) was generated as effect size by meta-analysis for continuous variants including IL-1β, IL-6, TNF-α, and CRP levels. Then according to study characteristics by dietary patterns of the intervention, subgroup analyses were performed. Results: Finally, 13 studies comprising a total of 1101 participants were included for the meta-analysis. IL-6 levels in dietary patients were significantly lower than controls (SMD = -0.30, 95% CI = -0.55, 0.04, p=0.02, I2 = 64% ). However, IL-1β, TNF-α, and CRP levels did not change significantly compared with the control group. Sensitivity analyses further yielded similar results. Conclusions: Dietary intervention may help decrease IL-6 rather than IL-1β or TNF-α or CRP levels in patients with MetS. Keywords Diets, inflammatory markers ,IL-6, metabolic syndrome, meta-analysis